Aortic valve type and calcification as assessed by transthoracic and transoesophageal echocardiography. (29th May 2014) - Yousry, Mohamed; Rickenlund, Anette; Petrini, Johan; Jenner, Jonas; Liska, Jan; Eriksson, Per; Franco‐Cereceda, Anders; Eriksson, Maria J.; Caidahl, Kenneth
Summary Introduction Aortic valve calcification (AVC) may predict poor outcome. Bicuspid aortic valve (BAV) leads to several haemodynamic changes accelerating the progress of aortic valve (AV) disease. Aims To compare the diagnostic accuracy of transoesophageal echocardiography (TEE) and transthoracic echocardiography (TTE) in the assessment of aortic valve phenotype and degree of AVC, with intra‐operative evaluation as a reference. Methods We examined 169 patients (median age 65 years, 51 women) without significant coronary artery disease undergoing AV and/or aortic root surgery. TTE was performed within a week prior to surgery and TEE at the time of surgery. Results Compared with surgical AVC assessment, visual evaluation using a 5‐grade scoring system and real‐time images showed a higher correlation (TTE r = 0·83 and TEE r = 0·82) than visual (TTE r = 0·64 and TEE 0·63) or grey scale mean (GSMn) (TTE r = 0·63 and TEE r = 0·52) assessment of end‐diastolic still frames. AVC assessment using real‐time images showed high intraclass correlation coefficients (TTE 0·94 and TEE 0·93). With regard to BAV, TEE was superior to TTE with a higher interobserver agreement, sensitivity and specificity (0·86, 92% and 94% versus 0·57, 77% and 82%, respectively). Conclusion Semi‐quantitative AVC assessment of real‐time cine loops from both TEE and TTE correlated well with intra‐operative evaluation of AVC. Applying a predefined scoring system for AVC evaluation assures a high interobserver correlation. TEE was superior to TTE for evaluation of valve phenotype and should be considered when a diagnosis of BAV is clinically important.